A novel angiographic classification for the endovascular recanalization of symptomatic nonacute extracranial vertebral artery occlusion. (15th March 2021) - Gao, Feng; Zheng, Hongbo; Guo, Xu; Sun, Xuan; Miao, Zhongrong
Abstract : Background: There remains major uncertainty regarding the optimal therapy for symptomatic nonacute extracranial vertebral artery occlusion (EVAO). Endovascular recanalization for EVAO is technically challenging, and limited data are available. This research aimed to report a multicenter clinical experience of endovascular recanalization for symptomatic nonacute EVAO and establish a novel angiographic classification. Methods: From June 2011 to December 2019, 50 symptomatic nonacute EVAO patients treated with endovascular recanalization in three regional referral stroke centers were retrospectively analyzed. All patients were categorized into four groups based on the angiographic classification. The rates of technical success, periprocedural complications, any stroke or death within 1 month, and follow-up data were assessed. Results: The rates of technical success, periprocedural complications, and any stroke or death within 1 month were 86.0% (43/50), 12.0% (6/50), and 4.0% (2/50), respectively. The recanalization rates gradually decreased from Type A to Type D (100%, 94.7%, 80%, and 63.6%, respectively; P=0.007). The EVAO patients in the Type A group with tapered stump and short-segment occlusions showed excellent recanalization effects, with 100% technical success rates and no complications. Conversely, the lowest recanalization rate of 63.6% (7/11) and the highest periprocedural complication rate of 27.3% (3/11) were observed for the Type D group. Conclusions: Endovascular recanalization for symptomatic nonacute EVAO is technically feasible, especially Type A EVAO patients, which can provide an alternative treatment option for recurrent vertebrobasilar ischemia despite optimal medical therapy. The angiographic categorization established in this study is conducive to the selection of suitable patients prior to treatment decision.